Yunus: Miskin Visi dan Tidak Misioner? - Sukirdi Yohanes; Seri Damarwanti (Sekolah Tinggi Theologia Nazarene Indonesia, 2020)
Jonah was not the ideal model, chosen to learn how Christian missionaries should be. The contrary response to the call to be a servant of God becomes an interesting study to find out the background that shapes and pushes his attitude. The principles described in this paper lead to a paradoxical condition between missionary idealism and conditions in the field. Through the principles of hermeneutics, especially literary analysis, background analysis, context analysis, and theology, it tried to be used to find answer to the problems in Jonah's attitude which is contrary to his responsibility as the Prophet of God. The final purpose of this paper is the strengthening of the existence of God as God who provides opportunities for repentant humans, which is manifested in forgiveness, acceptance, cancellation of punishment, and restoration of relations with humans. The practical principles are drawn from the discussion become the standard for how Christians should respond through submission to God's authority.